Pembinaan Akhlak Siswa Melalui Program Kejar (Kegiatan Jum’at Religius) Di UPT SPF SMP Negeri 1 Percut Sei Tuan - Rizki Rey Sandi; Afrahul Fadhila Daulai (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to describe the implementation of KEJAR (Religious Friday Activities) activities and analyze their role in fostering students' morals at the SPF UPT of SMP Negeri 1 Percut Sei Tuan. This study uses a descriptive qualitative approach. Research informants include the vice principal for curriculum, coordinator of Religious Friday activities, teachers, homeroom teachers, and students. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study indicate that the KEJAR (Religious Friday Activities) program is carried out routinely and planned every Friday morning before learning begins, through a series of donations, dhikr and prayers together, delivery of Islamic advice, and simple evaluations. The moral values ​​instilled include religiosity, discipline, responsibility, generosity, honesty, politeness, and social awareness. Teachers and school officials play an active role through habituation, role models, and supervision. Supporting factors for this activity include positive responses from students and parents, school support and active involvement of teachers, while obstacles include limited time, weather conditions and differences in students' levels of awareness.